Estudo fitoquímico de Rauia sp e Conchocarpus macrophyllus (Rutaceae) e avaliação da atividade antiparasitária de extratos e substãncias isoladas - Albarici, Tatiane Regina (2006)
This work involved the study of plant extracts of the Rutaceae species. Among 16 extracts tested in assays carried out with T. cruzi gGAPDH and L. tarentolae APRT enzymes and trypomastigote forms of T. cruzi, four showed significant activities at least in one of them. The petroleum ether extract of stems of Conchocarpus macrophyllus (CMCF) and the methanolic extract of leaves of Rauia sp (RFM) showed 94% and 75% of parasitic lyses on trypomastigote forms of T. cruzi. The methanolic extract of leaves of Rauia sp1 (RF1M) showed 74% of inhibition of gGAPDH enzyme and the dichloromethane extract of stems of Conchocarpus macrophyllus (CMCD) showed 74% of inhibition of APRT enzyme. The methanolic extract of leaves of Rauia sp1 (RF1M) showed 67,9% of inhibition on the APRT enzyme assay. The phytochemical study of Rauia sp allowed the isolation of 30 substances among them 4 are described for the first time, the coumarins 3-ethylrauianin and 5-methoxyrauianin and the alkaloids 7-hydroxy-8-methoxy-N-methylflindersine and 8- hydroxy-Nmethylflindersine that is described as a natural product at first time. Among them 26 have already been described in the literature the coumarins murranganone, 7- methoxy-8-(2-acetyloxy-3-methyl-1-oxobut-2-enyl)-coumarin, isomurranganone, murralongin, murrangatin, munomicrolin, murrangatin diacetate, rauianin, umbeliferone e isoescopoletin, the alkaloids N-methyl-4-methoxy-2-quinolone, mirtopsine, dictamine, γ-fagarine, skimmianine, Z-dimethylrhoifolinate, zantobungeanine, zantodioline and veprissine, the amides paprazine and N-transferuloyltyramine, the flavone 3,7,4 -trimethoxy-5-hydroxyflavone, the lignan siringaresinol, the fenolic coumpound vanilic acid and the steroids β-sitosterol and stigmasterol. The phytochemical study of Conchocarpus macrophyllus allowed the isolation of 4 substances the alkaloids arborinine and methylarborinine and the steroids β-sitosterol and stigmasterol. Among the substances tested in one or more assays none of them showed satisfactory results, leading to conclude that either the active compounds have not been isolated or their activity is related to the combination effects.